Between Panama, Pandora, and Other Asteroids (GESTIÓN Y TENDENCIAS, 2022)
In astronomical terms, the distance separating Panama (Earth) from the planet Pandora in the film Avatar is 6 light years, roughly 5.676 x 10^13 km. However, from the perspective of the compromising documents produced by the International Consortium of Investigative Journalists (ICIJ) —known as the Panama Papers in 2015 and the Pandora Papers released on 3 October 2021— in terms of the contents, commitments, agreements, responsibilities, intentions, principles, and values recorded in them, it would appear that both idyllic, paradisiacal places are in fact neighbors.
Keywords: International Consortium of Investigative Journalists; Panama Papers; Pandora Papers